A melanin-inspired robust aerogel for multifunctional water remediation. Issue 3 (24th January 2023) - Yang, Peng; Bai, Wanjie; Zou, Yuan; Zhang, Xueqian; Yang, Yiyan; Duan, Gaigai; Wu, Jinrong; Xu, Yuanting; Li, Yiwen
Abstract : Inspired by the melanin in nature, a robust all-in-one aerogel was construct for organic dye and heavy metal ion contaminant adsorption, oil–water separation and solar-driven steam generation to achieve multifunctional water remediation. Abstract : Solar-driven vapor generation has emerged as a promising wastewater remediation technology for clean water production. However, the complicated and diversified contaminants in wastewater still restrict its practical applications. Herein, inspired by the melanin in nature, a robust aerogel was facilely fabricated for multifunctional water remediation via a one-pot condensation copolymerization of 5, 6-dihydroxyindole and formaldehyde. Benefiting from the superhydrophilicity, underwater superoleophobicity, and synergistic coordination effects, the resulting aerogel not only showed excellent performances in underwater oil resistance and oil–water separation ability, but also removed organic dyes and heavy metal ions contaminants in wastewater simultaneously. Moreover, owing to its admirable light harvesting capacity and porous microstructure for fast water transportation, the aerogel-based evaporator exhibited an excellent evaporation rate of 1.42 kg m −2 h −1 with a 91% evaporation efficiency under 1 sun illumination, which can be reused for long-term water evaporation. Note that such a stable evaporation rate could be maintained even in wastewater containing complex multicomponent contaminants. Outdoor evaporation experiments for lotus pond wastewater under natural sunlight also proved its great potential in practical applications. All those promising features of this all-in-one melanin-inspired aerogel may provide new strategies for the development of robust photothermal devices for multifunctional solar-driven water remediation.